Shear Capacity of High-Strength Bolts in Long Connections - Tide, Raymond H.R. (Engineering Journal, 2017)
Current design codes reduce the shear strength of individual bolts to account for potentially uneven distribution of force among the bolts including a 0.75/0.90 (83.3%) step function at 38 in. Available test data indicate there is no justification for a bolt shear strength reduction, especially the step function, due to the length of connection, provided that second-order effects are limited and gross and net section areas slightly exceed the AISC Specification limits (2010). A practical, empirical solution is proposed that maintains a reliability, ?, slightly greater than 4.0 for all connection lengths, using the current AISC resistance factor, ?, of 0.75.